If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3(2 + -3x) = 4(x + -4) + -17 4x + (2 * -3 + -3x * -3) = 4(x + -4) + -17 4x + (-6 + 9x) = 4(x + -4) + -17 Reorder the terms: -6 + 4x + 9x = 4(x + -4) + -17 Combine like terms: 4x + 9x = 13x -6 + 13x = 4(x + -4) + -17 Reorder the terms: -6 + 13x = 4(-4 + x) + -17 -6 + 13x = (-4 * 4 + x * 4) + -17 -6 + 13x = (-16 + 4x) + -17 Reorder the terms: -6 + 13x = -16 + -17 + 4x Combine like terms: -16 + -17 = -33 -6 + 13x = -33 + 4x Solving -6 + 13x = -33 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -6 + 13x + -4x = -33 + 4x + -4x Combine like terms: 13x + -4x = 9x -6 + 9x = -33 + 4x + -4x Combine like terms: 4x + -4x = 0 -6 + 9x = -33 + 0 -6 + 9x = -33 Add '6' to each side of the equation. -6 + 6 + 9x = -33 + 6 Combine like terms: -6 + 6 = 0 0 + 9x = -33 + 6 9x = -33 + 6 Combine like terms: -33 + 6 = -27 9x = -27 Divide each side by '9'. x = -3 Simplifying x = -3
| 5.05t=1.48t-3.57 | | -7/2r=-63/8 | | 2x+2y+3x+6y= | | 2(x-4)=2x+11 | | z+8=12-z | | Z=a-b+c | | 0=56x^2-72x+144 | | 16x^2-4x+252=0 | | 3/17=x/7 | | x=3-14 | | -2x=-54 | | (V+3)2=28 | | 4y-40=8y | | ((5Y^6)/(3Y^4))^(1/5) | | 4-y+2=-4 | | 17x^2+11x-6=0 | | 2(q-29)=1/2(4-8q) | | 3n^2=-12n-7 | | v+3squared=28 | | 5x-7/4=1/3 | | 6x+3=8x-17 | | Y=x^2+6-1 | | 10x+73+6x=-15+x | | -1=3+4k | | 3[2(x-3)+2]+5(x-3)=0 | | 5x+2(x+4)=60+3x | | 8.4-0.7t+2.2-1.4t=9-2.1t-6.4 | | 6(x-7)=12(x+4) | | f(2)+f(3)=f(5) | | -k+17=1 | | 6t^2+5t-4= | | 6x+2y=1356 |